The Relationship between Unemployment Rates and Enrollment at Private and Public Institutions in Georgia Before and After the Establishment of the HOPE Scholarship - Wilmoth, Wendy Sue (My University, 2014)
The positive correlation of unemployment and college enrollment rates is a widely held assumption. This dissertation tests this assumption by comparing unemployment rates and changes in 4-year college enrollments, both undergraduate and graduate, in Georgia for the years 1980-2008. Special attention is given to the differences in the enrollment dynamics of public and private institutions. The variable of the HOPE Scholarship, established in 1993 and somewhat unique to Georgia, was added to determine its influence on the relationship between unemployment and college enrollment. The central theoretical framework for this paper is Human Capital Theory, which proposes that a loss of human capital often inspires capital-building activities such as education. Pearson correlations were performed on Georgia unemployment rates and the graduate and undergraduate enrollment at all Georgia institutions that meet certain criteria. Results were mixed, with very little relationship being shown between HOPE and the unemployment/enrollment correlation among private institutions. HOPE appears to have had a neutralizing effect on negative correlations in public institutions, but did not generally produce significant positive correlations. Recommendations include relaxing certain eligibility standards for HOPE, establishing programs to retain HOPE scholars at risk of losing their eligibility, and, at private institutions, increasing discounting through no-loan policies that encourage enrollment in difficult economic times.
Chapter I INTRODUCTION.......................................................................................1 Chapter II REVIEW OF LITERATURE …………………………………………….8 Human Capital…………………………………………………………….8 Human Capital and Post-Secondary Education………………….............10 Economic Conditions and College Enrollment…………..……………...15 Economic Conditions and Private Colleges…………………………….. 19 The HOPE Scholarship Program………………………………………...20 Chapter III RESEARCH METHODOLOGY…………………………………….......25 Definitions……………………………………………………………….25 Subjects………………………………………………………………….26 Data Sources……………………………………………………………..29 Limitations and Delimitations……………………………………...…....30 Hypotheses and Variables………………………………………………..31 Instrumentation and Procedures……………………………………….....33 Chapter IV RESULTS………………………………………………………………..35 All Institutions…………………………………………………………...35 Undergraduates…………………………………………………………..35 Graduates ………………………………………………………………..36 Bachelor’s Institutions: Undergraduates………………………………...37 Master’s Institutions: Undergraduates …………………………………..38 Doctoral Institutions: Undergraduates………………………………….. 39 Bachelor’s Institutions: Graduates………………………………………40 Master’s Institutions: Graduates…………………………………………40 Doctoral Institutions: Graduates…………………………………………41 Chapter V DISCUSSION.……………………………………………………….......42 Undergraduate Enrollments……………………………………………...42 Graduate Enrollments …………………………………………………...46 Carnegie Classifications…………………………………………………48 Possible Circumstances in 2009-2013…………………………………...52 Possible Influence of 2011Changes to HOPE…………………………...53 Recommendations for Policymakers…………………………….............54 Implications for Private Institutions……………………………………..56 Recommendations for Private Institutions………………………………58 Implications for Public Institutions………………………………………61 Recommendations for Public Institutions………………………………..63 Chapter VI CONCLUSION…………………………………………………………..65 REFERENCES………………………………………………………………………..…71
Keywords: HOPE; Scholarships; Universities and colleges--Admission--United States--Georgia; Unemployment--United States--Georgia